Peran Artificial Intelligence dalam Mendukung Proses Pembelajaran di Perguruan Tinggi - In'am Isro'ati Marzuuqoh ZA; Agus Lestari (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The era of Industry 4.0 has accelerated digital transformation, with Artificial Intelligence (AI) emerging as a transformative technology in the higher education ecosystem. However, the rapid development of research has led to fragmentation of the literature and inconsistent empirical findings regarding its implementation. This Systematic Literature Review (SLR) aims to consolidate current evidence to map the forms of AI applications, analyze their impacts and challenges, and synthesize recommendations for AI implementation as a learning assistant in higher education institutions. By adopting the PRISMA protocol, the literature search was conducted on indexed databases such as Scopus, Google Scholar, and ERIC using a combination of keywords related to AI and higher education. A total of 15 empirical and conceptual studies published between 2023 and 2025 met the inclusion criteria for thematic analysis. The main findings reveal that AI is primarily implemented in the form of virtual assistant chatbots, intelligent tutoring systems, and adaptive learning platforms, which significantly contribute to improving learning process efficiency, personalizing materials, and providing responsive feedback. On the other hand, AI integration is also faced with complex challenges, including plagiarism vulnerabilities, data security issues, technology dependency, and the digital competency gap among educators. The implications of this synthesis emphasize the urgency of developing comprehensive institutional policy frameworks, strategic training programs for educators, and strengthening ethical principles in the use of AI to ensure optimal and sustainable integration in higher education environments. Keywords: Artificial Intelligence, Learning Assistants, Learning Personalization, Digital Transformation, AI Implementation. Abstrak Era Revolusi Industri 4.0 telah mengakselerasi transformasi digital, di mana Artificial Intelligence (AI) muncul sebagai teknologi transformatif dalam ekosistem pendidikan tinggi. Namun, perkembangan pesat penelitian mengakibatkan fragmentasi literatur dan inkonsistensi temuan empiris mengenai implementasinya. Systematic Literature Review (SLR) ini bertujuan untuk mengkonsolidasi bukti-bukti terkini guna memetakan bentuk aplikasi, menganalisis dampak dan tantangan, serta menyintesis rekomendasi implementasi AI sebagai asisten pembelajaran di perguruan tinggi. Dengan mengadopsi protokol PRISMA, penelusuran literatur dilakukan pada basis data terindeks seperti Scopus, Google Scholar, dan ERIC menggunakan kombinasi kata kunci terkait AI dan pendidikan tinggi. Sebanyak 15 studi empiris dan konseptual yang terbit antara tahun 2023 hingga 2025 memenuhi kriteria inklusi untuk dianalisis secara tematik. Temuan utama mengungkapkan bahwa AI diimplementasikan terutama dalam bentuk asisten virtual berbasis chatbot, sistem tutor cerdas, dan platform pembelajaran adaptif, yang berkontribusi signifikan terhadap peningkatan efisiensi proses belajar, personalisasi materi, dan responsivitas umpan balik. Di sisi lain, integrasi AI juga dihadapkan pada kompleksitas tantangan, termasuk kerentanan plagiarisme, isu keamanan data, ketergantungan teknologi, dan kesenjangan kompetensi digital pendidik. Implikasi dari sintesis ini menekankan urgensi pengembangan kerangka kebijakan institusional yang komprehensif, program pelatihan strategis bagi pendidik, dan penguatan prinsip etika dalam pemanfaatan AI untuk memastikan integrasi yang optimal dan berkelanjutan di lingkungan perguruan tinggi. Kata Kunci: Artificial Intelligence, Asisten Pembelajaran, Personalisasi Pembelajaran, Transformasi Digital, Implementasi AI.